Classroom Interaction Patterns in English Foreign Learner (EFL) Study at Senior High School of As’ad Jambi - Fauzi Atunnisa; Failasofah Failasofah; Bunga Ayu Wulandari (UM Purwokerto Press, 2024)
This research examines the patterns of classroom interaction and the speech functions used in English as a Foreign Language (EFL) classes at MAS As’ad, Kota Jambi. The research utilizes a descriptive qualitative approach to analyze spoken interactions between teachers and 11th-grade students, with data collected through classroom observations and video recordings. The analysis is guided by Sinclair and Coulthard’s (1992) classroom interaction model, Walsh’s (2011) framework on classroom interactional competence, and Eggins and Slade’s (1997) categorization of speech functions. The study identifies the prevalent interaction patterns in the classroom and investigates how these patterns facilitate or hinder students' language learning. The findings revealed five distinct patterns of interaction: (1) teacher eliciting exchange, (2) teacher directing exchange, (3) teacher informing exchange, (4) student eliciting exchange, and (5) student informing exchange. The speech functions exhibited a variety of moves between the teacher and students, with both parties contributing almost equally to the interaction, indicating a well-maintained exchange process. These findings suggest that classroom interaction patterns significantly influence student participation, providing opportunities for comprehensible input and feedback. Further research is recommended to explore the impact of these interaction patterns on students' academic achievement. By highlighting the importance of balanced communication roles and the need for meaningful interaction, this research offers valuable insights for educators aiming to improve classroom dynamics and foster a more engaging learning experience.